Inhibitor Transient Receptor Potential Vanilloid Type 1: Penggunaan Topikal pada Berbagai Dermatosis - Muhammad, Parikesit; Paramitha Wibawa, Larisa; Keumala Budianti, Windy; Legiawati, Lili; Menaldi, Sri Linuwih; Rosdiana, Dewi Selvina (Universitas Kristen Krida Wacana, 2024)
Transient receptor potential vanilloid type 1 (TRPV1) plays an important role in the pathophysiology of pruritus and pain. TRPV1 inhibitors can reduce the sensation of itching and pain by blocking nociceptive signals from peripheral nerve fibers to the central nervous system. Topical TRPV1 inhibitors is also thought to improve skin barrier function. Therefore, TRPV1 inhibitors are considered as potential therapy in various dermatoses. Topical TRPV1 inhibitors that are currently being studied are asivatrep for atopic dermatitis and trans-4-tert-butylcyclohexanol for various dermatoses associated with sensitive skin. Further studies with better quality and longer duration are needed to assess the efficacy and safety profile of TRPV1 inhibitors.